THE EFFECT OF QUENCHING TREATMENT BY VARIATION OF COOLING MEDIA (WATER, USED OIL, COOKING OIL) ON EGREK HARDNESS - Putri, Fenoria; Gunawan, Indra; Rizky, Dany Agung (Politeknik Negeri Sriwijaya, Indonesia, 2023)
By using water on the gilding, the blacksmith's Egrek was hardened. The Egrek must have tough hardness. The low hardness causes the Egrek to wear out frequently, so consumers criticize the hardness and toughness of blacksmith products. Due to the wrong heat treatment, the Egrek cause is easily destroyed. The purpose of this study was to determine the effect of quenching treatment with various cooling media such as water, used oil, and cooking oil on increasing the hardness of blacksmith products. This research method is an experimental quenching using water, used oil, and cooking oil at 800°C, 850°C, and 900°C, with a holding time of 30 minutes. Rockwell hardness test, statistical data processing using ANOVA and supported by the use of expert design software. Having an average carbon content of 0.379%, Egrek's raw material is made of medium carbon steel. Based on the results of the quenching process with water, used oil, and cooking oil affect hardness. The quenching process of the cooking oil cooling medium that occurs at 800°C with a hardness value of 50.1 HRC produces a minimum hardness value, while the maximum average hardness lies in the water cooling medium with a temperature of 900°C of 60.4 HRC. The results of the percentage contribution of each are used oil by 96.37%, cooking oil by 96.61%, while water cooling media contributed by 88.41%. So that the cooling media for used oil and cooking oil can also be used as an alternative choice of cooling media.